Microbial Inoculants in Sustainable Agriculture: Advancements, Challenges, and Future Directions - Alondra María Díaz-Rodríguez; Fannie Isela Parra Cota; Luis Alberto Cira Chávez; Luis Fernando García Ortega; María Isabel Estrada Alvarado; Gustavo Santoyo; Sergio de los Santos-Villalobos (Plants)
The rapid growth of the human population has significantly increased the demand for food, leading to the intensification of agricultural practices that negatively impact the environment. Climate change poses a significant threat to global food production, as it can disrupt crop yields and modify the lifecycle stages of phytopathogens and pests. To address these challenges, the use of microbial inoculants, which are bioproducts containing beneficial microorganisms known as plant growth promotion microorganisms (PGPMs), has emerged as an innovative approach in sustainable agriculture. This review covers the isolation and identification of beneficial strains, the screening and selection process, the optimization of production techniques, and the importance of quality control and field testing. It also discusses the key points for the development and formulation of high-quality microbial inoculants, as well as highlights their advancements, current challenges, and future directions for research and application.